Orality and Literacy in Early Christianity - Kelber, Werner H. (Biblical theology bulletin, 2014)
This review essay engages Pieter Botha's Orality and Literacy in Early Christianity in a wide-ranging discussion of the ancient and early Christian communications culture. It reviews and seeks to carry forward some of the author's principal ideas about voice and chirographic practices, oral-scribal interfaces, compositional processes and performative activities, authorship, and memory both as an individual and as a social force. The first part draws a stark difference between the modern typographic media world and the oral-scribal-memorial communication processes of antiquity, and it exposes a tendency in biblical studies to project key features of the former upon the latter. The second part focuses on two major issues. One is the development of the Jesus traditions with an emphasis on rumor transmission, an unofficial, uncontrollable, interactional process. The second issue concerns the compositional identity of Mark, posing a sharp alternative between Mark as autograph of oral traditioning vis-à-vis a scribally accomplished hermeneutical act of interpretation. The third part revisits Paul's practices of authoring, placing his letters firmly in the context of the ancient memorial-oral-scribal-performative network of communications.